2013
DOI: 10.4269/ajtmh.13-0011
|View full text |Cite
|
Sign up to set email alerts
|

Weight Gain and Response to Treatment for Multidrug-Resistant Tuberculosis

Abstract: Abstract. Alternatives to culture are needed in high burden countries to assess whether response to treatment of multidrug-resistant-tuberculosis (MDR-TB) is satisfactory. The objective was to assess the association of weight gain and treatment outcome. The methods included analysis of clinical, bacteriologic, and weight from 439 MDR-TB patients in the Philippines. Odds ratios (ORs) were calculated to determine whether 5% weight gain during the first 6 months of treatment was associated with outcome. Three hun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
30
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 12 publications
6
30
0
Order By: Relevance
“…One prior study showed that weight gain was associated with an improved clinical better response to MDR-TB drug treatment, which is consistent with our data in drug-sensitive subjects. (7) Despite a trend toward increased mean energy intake, individuals with MDR-TB gained significantly less body weight and fat-free mass. These data suggest that MDR-TB patients were more catabolic/less anabolic than the drug-sensitive TB patients, likely due to ineffective anti-TB drug treatment until second-line drugs were initiated approximately 8 weeks after diagnosis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One prior study showed that weight gain was associated with an improved clinical better response to MDR-TB drug treatment, which is consistent with our data in drug-sensitive subjects. (7) Despite a trend toward increased mean energy intake, individuals with MDR-TB gained significantly less body weight and fat-free mass. These data suggest that MDR-TB patients were more catabolic/less anabolic than the drug-sensitive TB patients, likely due to ineffective anti-TB drug treatment until second-line drugs were initiated approximately 8 weeks after diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…(1, 3, 5, 6) Body weight changes during treatment have been explored as a simple biomarker for both disease severity and treatment outcomes. (4, 7) Further, it has been shown that TB patients with low BMI (<18.5 kg/m 2 ) are at increased risk for TB-related mortality and treatment failure. (4, 7, 8) Despite the abundance of cross-sectional data on the relationship between drug-sensitive TB and body composition, there are few serial studies of body composition in TB(9, 10) or that combine dietary intake and body composition during anti-TB drug treatment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[29][30][31] Interestingly, patients with isolates resistant to pyrazinamide were found to be less likely to achieve culture conversion by 60 days. The introduction of the Xpert MTB/ RIF assay allowed for rapid diagnosis of MDR-TB treatment, particularly in patients with no overt signs of failure.…”
Section: Discussionmentioning
confidence: 99%
“…Weight monitoring during the first 6 months of treatment is also an important predictor of unfavourable outcome. 5 Poor adherence to monthly weight measurement, as reported in this study, thus fails to identify poor treatment outcome.…”
Section: Public Health Action Adherence To Mdr-tb Treatment Follow-upmentioning
confidence: 84%